Preparation of graphene oxide by cyanuric chloride as an effective and non-corrosive oxidizing agent. Issue 116 (14th December 2016) - Khani, M.; Mehdipour, E.; Faghani, A.; Guday, G.; Donskyi, I. S.; Unger, W. E. S.; Haag, R.; Adeli, Mohsen
Abstract : In this work, we report a new method for the synthesis of graphene oxide (GO) using cyanuric chloride as a non-corrosive oxidizing agent. Abstract : In this work, we report a new method for the synthesis of graphene oxide (GO) using cyanuric chloride as a non-corrosive oxidizing agent. The mild conditions, simple purification, and scalability of this method are significant advantages over common approaches in which harsh oxidizing agents are used. Moreover, a major drawback with the Hummers' method, the production of toxic gases, is not an issue with this process. This method is a safe and large-scale alternative for the production of GO under mild conditions.